Giant Multilocular-Cystic Metaplastic Thymoma: A Case Report - Han L; Gao B; Wang EH; Wang L (Dove Medical Press, 2023)
Lihua Han,1 Bo Gao,2 En-Hua Wang,3 Liang Wang3 1The Central Laboratory of Morphology, Shenyang Medical College, Shenyang, People's Republic of China; 2Department of Pathology, Cancer Hospital of China Medical University, Shenyang, People's Republic of China; 3Department of Pathology, First Affiliated Hospital and College of Basic Medical Sciences, China Medical University, Shenyang, People's Republic of ChinaCorrespondence: Lihua Han, The Central Laboratory of Morphology, Shenyang Medical College, Shenyang, People's Republic of China, Email hanlihualn@163.comAbstract: The metaplastic thymoma with giant multilocular-cyst formation had not been documented. The metaplastic thymoma is an extremely rare primary thymic epithelial tumor with an indolent clinical course. It is characterized by a histologic biphasic appearance, which is consisted of solid epithelial areas and spindle cells as the background. This specific pattern can be easily mistaken as the type A thymoma or the type A components of type AB thymoma. When cystic change occurs in metaplastic thymoma, it will bring more challenges for both imaging and pathological diagnosis. Herein, we reported an extremely rare case of a 14.9-cm giant tumor located in the anterior mediastinum of an elderly female. The tumor is consisted of both multilocular cysts and solid components, with the largest cyst measuring 6 cm in diameter. The multilocular cyst contained hemorrhage, calcification, and cholesterol crystal cracks without cell lining. In the solid area, the epithelial cell nests were surrounded by spindle cells with scattered lymphocytes. With immunostains, neither type of cells was CD20 positive. The epithelial cells were positive for CK and P63, while the spindle cells expressed vimentin and EMA. Fluorescence in situ hybridization analysis revealed that the tumor harbored YAP1-MAML2 gene fusions. Accordingly, although the multilocular cystic pattern set a diagnostic challenge, the diagnosis of metaplastic thymoma was rendered due to the immunohistochemistry staining and YAP1-MAML2 gene rearrangement detection.Keywords: metaplastic thymoma, thymoma, thymic cyst, FISH, YAP1-MAML2